Ppkausas, a Youth Digital Network that Defended the Neoliberal System - Rivas Frías, Bruno (2019)
The purpose of this article is to analyze the virtual social network formed by the young people who participated in the presidential campaign of Pedro Pablo Kuczynski in 2011. In order to achieve this objective, a qualitative methodolo-gy was applied that consisted of a field work composed of interviews in depth carried out to 24 members of the Young Generation PPK collective, the so-called ppkausas. As a result of the analysis, it was observed that this movement used virtual tools to generate a space that came out in defense of the hegemonic system. In conclusion, the case analyzed shows that youth networks can be spaces in which individuals whose subjectivities have been marked by the discourses of individualism are grouped.